PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP KETIDAKSESUAIAN PRODUK DISKON DALAM TRANSAKSI E-COMMERCE - Theresia Tamaria (2024)
E-commerce refers to electronic trade conducted through the web, encompassing the promotion of services and products. Despite the existence of security systems and regulations established by the Indonesian government, there are still vulnerabilities to fraudulent activities. An illustrative example includes the sale of products that do not align with the specified size descriptions, accompanied by the rejection of compensation claims under the pretext of discounted purchases. This situation underscores the consumer's weakened position in e-commerce transactions. This research delves into the legal protection afforded to consumers concerning discrepancies in discounted products within the realm of e-commerce and the legal consequences of businesses rejecting compensation claims when consumers purchase products during discounted periods. The employed methodology in this study is juridical-normative. The findings of this research indicate that consumers are entitled to receive products in accordance with the ordered specifications, and e-commerce businesses bear responsibility under the Consumer Protection Law (UUPK). E-commerce platforms need to reassess their rejection of compensation for non-compliant products, necessitating increased oversight and stricter regulations to ensure compliance with the UUPK and promote responsible business practices.